Insights into the flow field and performance of a boundary layer pump - Rajendran, David John; Palaveev, Kyril; Anselmi Palma, Eduardo; Santhanakrishnan, Mani Sekaran; Pachidis, Vassilios (American Society of Mechanical Engineers (ASME), 2024)
A flow field analysis of a realistic, integrated, multi-disc boundary layer pump as is necessary for investigating the reasons for typically quoted low efficiencies in such pumps is described. The study focuses on the 3D RANS solutions of a water boundary layer pump model created to replicate a design which consists of 170 discs and a volute channel. A baseline study is performed to investigate the rotor-only and volute-only flow fields and identify the losses in each as separate systems. Thereafter, an integrated model is characterized for different operating conditions. The flow fields of all three models are discussed and the results of the integrated model are compared to the experimental data. The results from the rotor-only model confirm the typically made claim that the rotor efficiency is relatively high, which in this case is 87% at the design point. The volute on its own indicated a hydraulic efficiency of ~97%. However, the integrated model yielded a rotor efficiency of ~74% and an overall pump efficiency of 51% at the design point, clearly outlining the fact that the effect of the volute integrated with the rotor is the reason for both the rotor and pump efficiency degradation. The reason for this drop in efficiency is discussed by highlighting the change in the flow topologies. The insights into the flow field and the identification of the reason for inefficiencies using a separated component analysis approach provides directions for avenues in which design improvements need to be attempted.
Keywords: boundary layer pump; Tesla pump; friction pump; computational fluid dynamics